Correlation between preoperative axillary ultrasound and histopathology of resected lymph nodes in patients with carcinoma breast - Wani, Ab. Hamid; Gupta, Anish; Dhigra, Nasib Chand; Sing, Narinder; Iqbal, Javid (International Journal of Research in Medical Sciences, 2018)
Background: Axillary Ultrasound is an important tool in assessing regional lymph node status in women who are node negative clinically as many of them will prove to have axillary lymph node involvement on histopathology. The aim of the present study was to establish the role of axillary ultrasound in preoperative assessment of lymph node status in women with carcinoma breast and to correlate the findings of axillary ultrasound with the histopathology of resected axillary nodes. Methods: Forty patients (all women) were included in this study and the preoperative axillary ultrasound was done to know the status of axillary lymph nodes and the findings were correlated with histopathological findings of the resected nodes. Results: The sensitivity of axillary ultrasound was found to be 66.67%, specificity was 87.5%, accuracy 75%, positive predictive value (PPV) of 88.89% and negative predictive value of 63.4%. Conclusions: Axillary ultrasound is very important tool in assessing preoperative axillary lymph node status in patients with carcinoma breast. It is also important in assessment after inadequate axillary dissection and for follow up of non-treated axilla.